The relationships among the pulse rate, use of beta-blockers, and prognosis in patients with ischemic heart disease in a real-world database using a storage system. (14th October 2021) - Oba, Y; Kohro, T; Sato, H; Nochioka, K; Nakayama, M; Fujita, H; Mizuno, Y; Kiyosue, A; Iwanaga, Y; Miyamoto, Y; Matoba, T; Tsutsui, H; et al.
Abstract: Background: The use of β-blockers has the effect of improving the prognosis of patients with ischemic heart disease (IHD). One of the underlying mechanisms is a decrease in the cardiac load due to a reduction in the heart rate. Purpose: To clarify the relationships among the pulse rate, the use of β-blockers, and the prognosis in patients with IHD in a multicenter study using a storage system. Methods: The Clinical Deep Data Accumulation System (CLIDAS) collects (1) basic patient information, prescriptions, and laboratory data from electronic medical records from the Standardized Structured Medical Information eXchange (SS-MIX2) standard storage, and (2) the results of physiological tests, cardiac catheterization, and cardiac catheter intervention reports from the SS-MIX2 extended storage. 8540 cases who underwent cardiac catheterization from 6 university hospitals and the national cardiovascular center in Japan were registered (male: 77%, average age: 70.2 years). We evaluated these patients' pulse rate at admission and at the discharge of cardiac catheterization in 6, 598 patients. We divided the pulse rates at discharge into quartiles (Q1: <60, Q2: 60–66, Q3: 67–75, Q4: ≥76 bpm), and we analyzed the relationship between the pulse rate and the prognosis by dividing the patients into the stable angina group (n=2, 631) and the acute coronary syndrome (ACS) group (n=2, 394). Regarding the use of β-blockers, we compared the pulse rates of the patients taking carvedilol (n=1, 728) and those taking bisoprolol (n=2, 761) at admission and discharge. Major adverse cardiovascular events (MACE) were defined as cardiovascular death, non-fatal myocardial infarction, unstable angina, heart failure, stroke, and other hospitalized cardiovascular events. Results: A total of 600 MACEs occurred during an average observation period of 890 days. The incidence of cardiovascular events was significantly higher in the Q4 patients in the stable angina group (hazard ratio 1.79, 95% confidence interval 1.32–2.41, but there was no significant difference among the four pulse rate subgroups in the ACS group. The bisoprolol-treated patients had lower pulse rates at discharge (67.4±12.2 vs. 68.8±11.8 bpm, p<0.001) and a lower percentage of patients in the Q4 group (21.2 vs. 24.9%, p=0.005) compared to the carvedilol-treated patients. The pulse rate at admission was similar in the bisoprolol- and carvedilol-treated patients (74.3±19.3 vs. 73.2±29.5 bpm, p=0.328). Conclusion: In a real-world database using a storage system, a pulse rate of ≤75 bpm was associated with a good prognosis in patients with ACS. Compared to carvedilol, bisoprolol was associated with a decreased pulse rate at discharge. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Kowa Company, Ltd.